Bulky Condyloma Acuminata following Ustekinumab Treatment for Plaque Psoriasis: A Case Report - Martina Burlando; Mattia Fabio Molle; Emanuele Cozzani; Aurora Parodi (Karger Publishers, 2021)
Ustekinumab is a fully human monoclonal antibody targeting the pro-inflammatory cytokines interleukin (IL)-12 and IL-23 approved for the treatment of psoriasis and psoriatic arthritis. We report a case of a patient treated for chronic plaque psoriasis with ustekinumab who developed bulky condyloma acuminata shortly after initiating the treatment. Although ustekinumab has already been described in literature associated with other forms of human papilloma virus skin infections, this is the first case to our knowledge in which ustekinumab is associated with genital warts.